The Chagas non-endemic (ChaNoE) cohort: Aims and study protocol - Pau Bosch-Nicolau; Juan María Herrero-Martínez; Marta Arsuaga; Sandra Chamorro-Tojeiro; Irene Carrillo; Carlos Bea-Serrano; Jara Llenas-García; Sandra Pérez-Recio; Elia Fernández-Pedregal; Clara Crespillo-Andújar; Aroa Silgado; Ana Pérez-Ayala; et al. (PLoS ONE, 2025)
Chagas disease (CD), caused by Trypanosoma cruzi, is a neglected tropical disease with significant public health implications. While its primary transmission occurs in endemic regions via triatomine vectors, migratory processes have led to an increased prevalence in non-endemic areas as in Spain where an estimated 50,000 people live with CD. Chronic Chagas cardiomyopathy (CCC) and digestive complications are the primary manifestations, yet diagnostic criteria, especially regarding organic involvement, and treatment indications are still a matter of debate. There is an urgent need for standardized approaches to improve care and identify biomarkers for progression and treatment response. The Chagas non-endemic cohort (ChaNoE) aims to recruit individuals with chronic CD across multiple centers in Spain. Inclusion criteria involve a confirmed diagnosis based on two serological tests. Participants will receive comprehensive diagnostic evaluations, including electrocardiography, echocardiography, and periodic serological and PCR assessments. Follow-up will focus on disease progression, particularly CCC and digestive involvement, using standardized protocols. The study also establishes a biobank for serum samples to facilitate biomarker research. The ChaNoE cohort addresses critical gaps in the understanding of CD in non-endemic regions. By standardizing diagnostic and treatment protocols, it seeks to harmonize care and enable comparisons with cohorts in endemic areas. The creation of a biobank supports the identification of biomarkers for disease progression and treatment efficacy, a current unmet need in CD management. This initiative also strengthens research networks and informs public health strategies to mitigate the burden of CD in non-endemic settings. Findings will be disseminated to key stakeholders to improve the clinical and epidemiological understanding of this neglected disease.